2021
DOI: 10.3389/fmars.2021.678074
|View full text |Cite
|
Sign up to set email alerts
|

Companions and Casual Acquaintances: The Nature of Associations Among Bull Sharks at a Shark Feeding Site in Fiji

Abstract: Provisioning activities in wildlife tourism often lead to short-term animal aggregations during the feeding events. However, the presence of groups does not necessarily mean that individuals interact among each other and form social networks. At the Shark Reef Marine Reserve in Fiji, several dozen bull sharks (Carcharhinus leucas) regularly visit a site, where direct feeding is conducted during tourism driven shark dives. On 3,063 shark feeding dives between 2003 and 2016, we visually confirmed the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
1
5
1
Order By: Relevance
“…We found that social factors sometimes had similar effects on movement networks to environmental variables. While the bull shark has been found to form occasional aggregations around fish farms (Loiseau et al, 2016) or at artificial provisioning sites (Bouveroux et al, 2021), it is not recognized as displaying collective behaviours and strong patterns of spatial segregation have been found in our study population (Mourier et al, 2021). However, we found that more movements occurred through bull shark hotspots.…”
Section: Effects Of Social Environment On Movementscontrasting
confidence: 70%
“…We found that social factors sometimes had similar effects on movement networks to environmental variables. While the bull shark has been found to form occasional aggregations around fish farms (Loiseau et al, 2016) or at artificial provisioning sites (Bouveroux et al, 2021), it is not recognized as displaying collective behaviours and strong patterns of spatial segregation have been found in our study population (Mourier et al, 2021). However, we found that more movements occurred through bull shark hotspots.…”
Section: Effects Of Social Environment On Movementscontrasting
confidence: 70%
“…This approach proved effective in habituating the blacktip individuals to the observer's presence, with the result that they exhibited fairly natural behaviour during encounters without food provisioning. The use of provisioning to facilitate the observation of sharks has since been used by other researchers in Polynesia [19,20] and various other regions [21].…”
Section: Methodsmentioning
confidence: 99%
“…However, FIJ was not the only isolated sampling location; Seychelles is ~1000 km apart from Madagascar, yet it did not show traces of genetic isolation. Sampling bias could explain FIJ genetic differentiation, as most samples used here came from intermittently resident females suspected to pup in the area (Bouveroux et al, 2021;Brunnschweiler & Barnett, 2013;Cardeñosa et al, 2017;Glaus et al, 2019). Given the suspected reproductive philopatric behaviour of C. leucas females (Devloo-Delva et al, 2023;Espinoza et al, 2016;, the Fijian genetic distinctiveness could stem from relatedness, as in Lemon sharks (Feldheim et al, 2014).…”
Section: Population Structuringmentioning
confidence: 99%